Perancangan Company Profile Sebagai Media Promosi PT Bhineka Advertising - Oscar Ade Gunawan; Masnuna Masnuna (Student Research Journal, 2023)
PT Bhineka Advertising is a company operating in the advertising sector, which produces branding needs such as signs, banners, embossed letters, and so on. Bhineka Advertising realizes that there is a need for promotional efforts to promote their name and introduce the company to the public, especially to the intended target audience. Therefore, Bhineka Advertising plans to design a company profile as a strategic step to introduce and promote their company name to the public. This step is expected to increase visibility and understanding of the company's identity, support business growth, and strengthen Bhineka Advertising's position in the advertising industry.